Rancang Bangun Aplikasi Computer Based Test (CBT) Untuk Membantu Siswa Dalam Melaksanakan Ujian - Rahayu, Sri Lestari; Sari, Rita Novita; Hayati, Ratna Sri; Surbakti, Muhammad Aditya (Publikasi Pengabdian Masyarakat, 2024)
The rapid development of information technology has driven its utilization in various activities, including the education sector. One of its applications is the Computer-Based Test (CBT) system, which replaces conventional paper-based exams. SMK PAB 8 Sampali faces challenges in conducting paper-based exams, such as the risk of grading errors and inefficiency in the process. Therefore, developing a CBT application is a potential solution to improve the quality of exam administration. This application allows students to easily complete exam questions using internet-connected devices, eliminating the need for additional writing tools. Teachers also benefit from a more efficient grading process and structured evaluation reports. This research aims to design and develop a CBT application to support exam administration at SMK PAB 8 Sampali, with the hope of providing significant benefits for students, teachers, and other users. Additionally, training provided by the researchers aims to enhance students' knowledge of the Computer-Based Test (CBT) application to assist them in taking exams.